“PENGARUH RETURN ON ASET (ROA), DEBT TO EQUITY RATIO (DER), ECONOMIC VALUE ADDED (EVA), TOTAL ASET TURNOVER (TATO), DAN CURRENT RATIO (CR) TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2017 – 2019” - Fransiska, Imelda; Ekadjaja, Agustin (Jurnal Paradigma Akuntansi, 2024)
This study aims to analyze the effect of ROA, DER, EVA, TATO and CR on stock returns in manufacturing companies listed on the IDX in 2017-2019. Descriptive research method, the population type of data used is secondary data. The conclusion of this study is the significance value of t for the ROA variable <0.05 with a coefficient value of 2877.397159 so that it means that ROA has a positive effect on stock returns, the coefficient value is 0.420729 so that it means that DER has no effect on stock returns, the significance value of t is for the EVA variable. <0.05 so EVA has a significant effect on Stock Return, the significance value of t for the TATO variable <0.05 with a coefficient value of 262.834290 so that it means that TATO has a positive effect on Stock Return, the significance value of t for the Currentratio variable > 0.05 with a coefficient value 0,449978 so that it means that Currentratio does not have a positive effect on Stock Return.”